Legal Protection of Work Safety Crimes Victims In Indonesia - Hamonangan Albariansyah; Topo Santoso; Eva Achjani Zulfa (Faculty of Law, Sriwijaya University, Indonesia, 2022)
Between 2014 and 2018, the Indonesian Ministry of Manpower recorded 89,625 cases of work accidents, and 1,193 of them resulted in death. During this period, 34,075 companies were reported for alleged work safety crimes. From the 2,074 cases, only four have been sentenced to prison. The most interesting issue is that the victims of work safety crimes do not get any kind of restitution or even compensation. This article aims to investigate the legal protection for victims of work safety crimes from the criminal law perspective. The method used is normative qualitative research on primary data, such as work safety legislation, the Criminal Code, and criminal court decisions. As a result, the work safety law stipulates that the purpose of law enforcement on work safety is recovery for victims, repairs and prevention. They are carried out to protect the public interest. Work safety regulations also regulate the qualifications of actions categorized as work safety crimes. Unfortunately, the regulation does not provide a mechanism for resolving work safety crimes. So that the settlement of work safety crimes relies on the general criminal justice system that adheres to retributive objectives in law enforcement. The purpose of law enforcement on work safety cannot be applied because victims do not get restitution or compensation. Thus, to obtain legal protection in accordance with the objectives of law enforcement on work safety, the alternative solution is a criminal policy to establish a special criminal mechanism for the settlement of work safety crimes.